Organizing Psycho-Oncological Care for Cancer Patients: The Patient’s Perspective - Schuit, Anouk S.; Holtmaat, Karen; van Zwieten, Valesca; Aukema, Eline J.; Gransier, Lotte; Cuijpers, Pim; Verdonck-de Leeuw, Irma M. (Frontiers in Psychology, 2021)
Background: Cancer patients often suffer from psychological distress during or after cancer treatment, but the use of psychological care among cancer patients is limited. One of the reasons might be that the way psychological care is organized does not fit patients’ preferences. This study aimed to obtain detailed insight into the preferences of cancer patients regarding the organization of psychological care for cancer patients. Methods: 18 semi-structured interviews were conducted among cancer patients who completed psychological treatment between 2015 and 2020 at the psychology department in a general hospital or a center specialized in psychological care for cancer patients. The interview comprised questions related to the preferences regarding the institute where to receive treatment, the psychologist who provides treatment, and the type of treatment, as well as questions related to experienced barriers and facilitators to receive psychological care. Interviews were digitally recorded and transcribed verbatim. Data were analyzed individually by two coders into key issues and themes. Results: Regarding the institute, easy accessibility and prompt availability of psychological care were considered important. Regarding the psychologist, most participants had a strong preference to be treated by a psychologist specialized in cancer or other somatic diseases. Individual face-to-face therapy was preferred above other types of treatment. Several barriers were mentioned to receive psychological treatment, among which poor accessibility to psychological care, lack of knowledge on the possibilities for psychological treatment related to cancer, and stigma. Most frequently mentioned facilitators were being assertive to ask for help, having a good relationship with the healthcare professional, and the integration of psychological support within medical cancer care. Conclusions: From the patient’s perspective, the organization of psychological care for cancer patients should focus on easy accessibility and availability, delivered by specialized psychologists, and integration in medical cancer care. Online and group therapy are acceptable but individual face-to-face therapy is preferred. It is warranted to increase awareness on psychological care targeting both patients and healthcare providers.